APPLICATION OF SCENARIO ANALYSIS IN THE INVESTMENT PROJECTS EVALUATION - Brzaković, Tomislav; Brzaković, Aleksandar; Petrović, Jelena (Economics of Agriculture, 2016)
Investing represents an investment in the present to achieve certain effects in the future, and risk is an essential part of the investment process. Scenario analysis involves key risk factors of the project, its sensitivity to changes in key factors and the likelihood of their changes. Scenario analysis allows us to assign probabilities to the base case, the best case and the worst case so that we can fnd the expected value and standard deviation of the projects NPV to get a better idea of the projects risk. The goal is to determine whether it is possible to make relevant investment decisions on the basis of the parameters of projects risk, such as the standard deviation and the coeffcient of variation. The paper is based on a mathematical model, applied to a specifc agricultural company. In our case, the project has a wide range of possibilities and a large potential negative value, which suggests a great risk of the project. Although the scenario analysis shows a higher risk, it is not clear if the project should be accepted or not, and therefore, it is necessary to conduct simulation analysis, in order to get reliable answers.